KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA KE FILM BULAN TERBELAH DI LANGIT AMERIKA KARYA SUTRADARA RIZAL MANTOVANI - Wahyuni, Fuji; Hayati, Yenni; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2017)
The purpose of this article (a) to describe story of episode novel Bulan Terbelah di Langit Amerika created by Hanum Salsabiela Rais and Rangga Almahendra, (b) to describe story of episode film Bulan Terbelah di Langit Amerika director by Rizal Mantovani, (c) to describe similiar and different story of episode novel with film Bulan Terbelah di Langit Amerika. The data of this study were story of episode novel Bulan Terbelah di Langit Amerika created by Hanum Salsabiela Rais and Rangga Almahendra and film Bulan Terbelah di Langit Amerika director by Rizal Mantovani. Analyzed  technique  do  with  ekranisasi  theory.  The findings of  the  study  showed  that  the  decrease  story  of  episode and sub episode novel Bulan Terbelah di Langit Amerika created by Hanum Salsabiela Rais and Rangga Almahendra in film Bulan Terbelah di Langit Amerika director by Rizal Mantovani become to  story of episode to 87 story of episode. Increase story of episode in film Bulan Terbelah di Langit Amerika director by Rizal Mantovani become to 32 story of episode. The same variation changes event, figure and background story ofepisode  in  novel  Bulan Terbelah di Langit Amerika created by Hanum Salsabiela Rais and Rangga Almahendra and  film  Bulan Terbelah di Langit Amerika director by Rizal Mantovani become to 25 story of episode.Keywords: novel, film, ecranization, story of episode